Quantitative analyses of maxillary sinus using computed tomography (Journal of Applied Oral Science, 2003)
The aim of this study was to evaluate the precision and accuracy of linear measurements of maxillary sinus made in tomographic films, by comparing with 3D reconstructed images. Linear measurements of both maxillary sinus in computed tomography CT of 17 patients, with or without lesion by two calibrated examiners independently, on two occasions, with a single manual caliper. A third examiner has done the same measurements electronically in 3D-CT reconstruction. The statistical analysis was performed using ANOVA (analyses of variance). Intra-observer percentage error was little in both cases, with and without lesion; it ranged from 1.14% to 1.82%. The inter-observer error was a little higher reaching a 2.08% value. The accuracy presented a higher value. The perceptual accuracy error was higher in samples, which had lesion compared to that which had not. CT had provided adequate precision and accuracy for maxillary sinus analyses. The precision in cases with lesion was considered inferior when compared to that without lesion, but it can't affect the method efficacy.